PENGARUH SISTEM INFORMASI AKADEMIK DAN KUALITAS LAYANAN TERHADAP KEPUASAN MAHASISWA DI POLITEKNIK ILMU PELAYARAN SEMARANG - Akhmad Ndori (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2015)
In establishing the satisfaction of university students, the institutions should improve the service qualitygiven to their students. The better of the service quality, the higher of the satisfaction towards the company. Theheight of the service quality is always in relation to the internal support of the institution, especially the supportof the human resource. From the satisfaction index done by Politeknik Ilmu Pelayaran Semarang, it is knownthat the point of satisfaction index of the students who are the academic service users of Politeknik IlmuPelayaran Semarang is far below from the target. This shows the low of service quality given in the institution.It is in line with the dimension of university students’ service which tends to decrease in 2011.The objective of the research is to analyze the influence of interaction between departments and theacademic information system to the service quality and to analyze the influence of interaction between departments,academic information system and service quality to the satisfaction of PIP Semarang students. Theresearch uses 120 respondents as the samples. The data is analyzed using SEM.Based on the data analysis, it is concluded that interaction between departments and academic informationsystem give positive influence to the service quality. The interaction between departments, academic informationsystem and service quality also give positive influence to the satisfaction of PIP Semarang students. Thestructured opportunities to the units in the institutions such as academic, finance, teaching and service to interacteffectively is created through the strategic planning about the service given to the students. Furthermore, thethings that can hinder the effective interaction between departments such as conflict between departments canbe avoided by arranging the organisation system of PIP Semarang in detail.Key words: Interaction between departments, Academic information System, Service Quality, Students Satisfaction